Comparative Impact of Yoga Practice on Lifestyle in Public and Private Sector Professionals - Suneel Kumar; Poonam Yadav (Recent Trends in Sports, 2024)
Yoga has become completely embedded in our lifestyle. Without yoga, it has become very difficult to stay healthy. Along with sports, yoga is also very important for human life. It keeps us in shape, active, and intellectually and socially rejuvenated. They impart discipline and coordination skills to us. Our camaraderie and brotherhood are also fostered via yoga and sports. Furthermore, it is crucial for both the physical and mental growth of our bodies. Only a healthy body can support a healthy mind. It showed that mean and standard of public sector deviation is 20.100 ± 5.740 and Standard Error Mean is 2.012 Public and Private Sectors Selected Public Sectors Private sector means and standard. The deviation is 22.44 ± 3.22 3 and the STD error mean is 1.450. The findings indicate that, at the 0.05 level of significance, the vocal propensity of the public sector obtained a value of 16.156, which is substantially greater than the tabulated "t" value of 2.145. The obtained value of vocal tendencyofthesectoris52.420andthisvalueissignificantlyhigherthanthe tabulated value 2.145 at the level of significance of0.05, it shows that male private sector has more vocal tendency than male public sector, the result shows that public The Sector' group mean is 24.300, and the Private Sector group mean is 22.44. Therefore, it may be said that men are more engaged in the private sector than in the public sector. The mean for the public sector group is 24.300, while the mean for the private sector group is 22.44, according to the results. Consequently, it can be inferred that men are more engaged in the private than in the public sectors. This demonstrates the possible advantages of incorporating sports and yoga into everyday routines for better health and productivity in a variety of fields.
Keywords: Assertiveness; Mental well-being; physical activity; private sector; public sector; sports and discipline